Morinda citrifolia compounds such elicitor substances of biochemical responses in melon plants: Morinda citrifolia compounds such elicitor substances of biochemical responses in melon plants. - Dias, Bruna Letícias; Dalcin, Mateus Sunti; Costa, Priscila Fonseca da; Santos, Patrícia Resplandes Rocha dos; Sousa, Rosangela Ribeiro de; Dias, Felipe Rocha; Mourão, Dalmarcia de Souza Carlos; Santos, Gil Rodrigues dos (Comunicata Scientiae, 2023)
Plants have complex structural and biochemical defense mechanisms that can be activated before or after the attack of phytopathogenic microorganisms. Among these mechanisms are the proteins related to the pathogenesis (PRP) and the hypersensitive response through the production of reactive oxygen species (ROS), which exist in enzymes capable of reducing its toxicity to the plant. In addition to activation induced by biotic or abiotic factors, such as compounds or substances that stimulate biochemical activity, called elicitor substances, such as essential oils and their constituents. Studies in the area are necessary to deepen knowledge and reach the technical and economic feasibility of its use for the benefit of sustainable agriculture. The aim was to evaluate the enzymatic activity of melon plants submitted to the noni essential oil application (EO) and octanoic acid (OA). In different treatment concentrations, as well as fungicide Cerconil® (0.2%) and Yantra® plant stimulant. The enzymes that had their activity evaluated were superoxide dismutase (SOD), chitinase (QUIT), ascorbate peroxidase (APX), and catalase (CAT). Octanoic acid (0.1%) and essential oil (0.5%) were the primary activators of the enzyme superoxide dismutase among the treatments tested. The enzyme ascorbate peroxidase had its production increased by the octanoic acid at 0.1%. EO was the primary activator of the catalase enzyme at 2% concentration. The secondary metabolites activity of the Morinda citrifolia against microorganisms and as an activator of the defense system were confirmed, considered a potential compound for developing a bioproduct as a substitute for pesticides.